(untitled) (Global Journal of Science Frontier Research, 2012)
The aim; of the present paper is to study a pathway fractional integral operator concerning with the pathway model and pathway probability density of some product of special functions. The results derived here are quite general in nature, and hence encompass several cases of interest.